Community assimilation: exploring dimension of Melaka tourism product / Mohamad Daim Darson...[et al.] - Darson, Mohamad Daim; Md. Hasim, Ahmad Khairuman; Adanan, Akmal; Mohd Kodri, Aida Nur (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2017)
This paper empirically examines the attributes of community assimilation towards Melaka Tourism in which covering several ethnics in this state. This study employed the attributes of community assimilation to assess the tourism product of Melaka. More specifically, this paper explores the element of community assimilation in Melaka through custom, language as well as food and beverages. Furthermore, the study is also conducted to determine the most influential factors of community assimilation that contributes to the Melaka tourism product. Data were collected from first and secondary resources through administered questionnaire survey and based on 362 respondents. The result from the correlation analysis shows that custom, language as well as food and beverages variables possess the explanatory power of the variation in Melaka tourism product. The testing process also confirms that food and beverages contribute high influence in Melaka tourism product. Finally, limitations of present findings were discussed, and implications for future studies are suggested.